Analysis of Organizational Commitments Based on Lecturer Characteristics - Bahdin Nur Tanjung; Elfrianto Elfrianto (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
This study aims to find out: 1) Differences in lecturer organizational commitment based on gender on permanent lecturers at University of Muhammadiyah Sumatera Utara, 2). Differences in lecturer organizational commitment based on experience or period of work for permanent lecturers at University of Muhammadiyah Sumatera Utara 3). Differences in lecturer organizational commitment based on interaction between gender and experience or period of work for permanent lecturers at University of Muhammadiyah Sumatera Utara. The study used a comparative descriptive method that is to analyze organizational commitments that are bound variables based on two sample groups namely the characteristics of lecturers of both gender and experience. Data was collected from a sample of as many as 40 male lecturers and 38 female lecturers using likert scale model quesionaries. The selected research design is a factorial design that is 2 x 2. A 2 x 2 factorial design using ANAVA analysis. His research results showed that gender, experience and interaction co-determined commitment to the organization.